Social and ecological dimensions are needed to understand human‐wildlife conflict in subsistence farming context - Yeshey; Rodney J. Keenan; Rebecca M. Ford; Craig R. Nitschke (People and Nature)
Abstract This study explores the social, economic and environmental dimensions of human‐wildlife conflict (HWC) in four districts of Bhutan. Looking beyond the common unidimensional approach to the evaluation of HWCs, it documents the multifaceted nature of HWCs through a social‐ecological system (SES) lens. We carried out a mixed method analysis of HWC based on 96 interviews consisting of qualitative and quantitative data and eight focus group discussions conducted in four districts representing four regions of Bhutan. Our case study finding reveals that HWC scenarios are complex and there is spatial variation in both social and ecological factors that contribute to HWC. In some areas, ecological aspects such as the composition and behaviour of wildlife species exacerbate the conflict, while in other regions the co‐occurrence of wildlife and livestock in the same ‘wild’ landscape drives HWC. The socio‐economic dimensions of HWC are largely driven by attitudes, tolerance, and behaviour of individuals underpinned by multiple factors. We propose that the SES approach improves our understanding of key social, economic and ecological factors, their interactions, and the feedback that either exacerbates or ameliorates HWC in contested landscapes. Read the free Plain Language Summary for this article on the Journal blog.